Analisis Dan Perancangan Sistem Informasi Administrasi Perizinan Penelitian Pada Badan Kesatuan Bangsa Dan Politik Provinsi Jambi - Haryadi, Fiet; Effiyaldi, Effiyaldi (Jurnal Manajemen Sistem Informasi, 2021)
The National Unity and Political Entity of Jambi Province is a Regional Government Organization (OPD) which has the main task "Implementing the preparation and implementation of regional acts in the field of National Unity and Politics". Limitations of Human Resources who are working on jobs that often occur delays in the process of issuing permissions, there are also events when to return data and preparation of reports because the storage is done manually, then search data is also long enough even difficult to find the data back, with archiving which is done in the data repeatedly damaged and damaged because it is needed can not be reused. Using the PHP programming language and using object-based modeling techniques diagrams, diagram diagrams, and activity diagrams. The output of this study. Licensing Information System Research At National Unity Agency And Politics of Jambi Province.